1990
DOI: 10.1177/009365090017003002
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Communication, Stress, and Burnout in the Workplace

Abstract: This research presents an integration of past research and theory that models the impact of stressful aspects of the workplace and key communication variables on employee burnout, occupational commitment, and work satisfaction. Two theoretical frameworks—social information processing theory (Salancik & Pfeffer, 1978) and uncertainty reduction theory (Berger & Calabrese, 1975)—are drawn on to propose a model in which communication variables lead to two stress variables then to burnout and finally to job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 35 publications
5
86
0
5
Order By: Relevance
“…First, it reduces workers' role stress (i.e., role ambiguity and role conflict) (Miller, Ellis, Zook, & Lyles, 1990;Ray & Miller, 1991). Because role stress often leads to burnout or turnover (Cordes & Dougherty, 1993;Mor Barak, Nissly, & Levin, 2001), supervisory communication indirectly influences worker burnout and turnover through its effect on perceived role stress.…”
Section: Abstract Supervisory Communication Burnout Turnover Intentmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it reduces workers' role stress (i.e., role ambiguity and role conflict) (Miller, Ellis, Zook, & Lyles, 1990;Ray & Miller, 1991). Because role stress often leads to burnout or turnover (Cordes & Dougherty, 1993;Mor Barak, Nissly, & Levin, 2001), supervisory communication indirectly influences worker burnout and turnover through its effect on perceived role stress.…”
Section: Abstract Supervisory Communication Burnout Turnover Intentmentioning
confidence: 99%
“…Miller et al (1990) discussed social information processing theory (Salancik & Pfeffer, 1978) and uncertainty reduction theory (Berger & Calabrese, 1975) as theoretical foundations with which to explain the role of supervisory communication in the process of burnout. First, the social information processing theory considers perceptions of the workplace to be a function of the communication environment in which workers are embedded, rather than a function of the objective characteristics of jobs and needs of workers (Salancik & Pfeffer, 1978).…”
Section: The Role Of Supervisory Communication In Information Processmentioning
confidence: 99%
“…Emotional exhaustion indicates an individual's stress reaction to social demands at work (Leiter, Clark & Durup, 1994), and is a measure of overextension and depletion of individuals' physical and psychological resources (Leiter & Harvie, 1998). Miller et al (1990) have previously used the seven-item scale (e.g., I feel used up at the end of the day; I feel burned out from my work) in the change communication literature. We used a 5-point response format ranging from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Emotional Exhaustion the Emotional Exhaustion Sub-scale Of mentioning
confidence: 99%
“…The strain caused by change leads to lowered job satisfaction and higher intentions to leave the organization (Johnson, Bernhagen, Miller & Allen, 1996;Schweiger & Denisi, 1991). For example, Miller, Ellis, Zook, and Lyles (1990) found that emotional exhaustion at work led to lower job satisfaction. Other research in various change contexts has found that better levels of mental and physical health indicators (Nelson, Cooper & Jackson, 1995) and less psychological strain (Parker et al, 1997) are correlated with higher levels of job satisfaction.…”
mentioning
confidence: 99%
“…Specific physical, cognitive, affective, motivational, behavioural, interpersonal and work symptoms are mentioned (Dubrin, 1990;Juntunen, Asp, Olkinuora, Arimaa, Strid & Kauttu, 1988;Pines et al, 1981;Schaufeli & Enzmann, 1998). The causes of burnout are classified in terms of the individual's profile and the work situation (Cherniss, 1995;Corrigan, Holmes, Luchins, Buican, Basit & Parks, 1994;Freudenberger, 1989;Golembiewski & Munzenrider, 1988;Landsbergis, 1988;Miller, Ellis, Zook & Lyles, 1990;Pines et al, 1981;Schaufeli & Enzmann, 1998). Coping with burnout is discussed in the literature on three levels, namely the individual, the interpersonal and the organisational levels (Cox & Ferguson, 1991;Muldary, 1983;Pines & Aronson, 1988;Schaufeli & Janczur, 1994).…”
mentioning
confidence: 99%